1995
DOI: 10.1111/j.1464-410x.1995.tb07341.x
|View full text |Cite
|
Sign up to set email alerts
|

The National Prostatectomy Audit: the clinical management of patients during hospital admission

Abstract: The clinical management of prostatectomy has been defined in a large and representative UK sample. In some circumstances consistent variations have been identified. It is not yet clear whether these variations influence outcome. These data can be used by surgeons wishing to compare their own patient management with that described here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 15 publications
3
47
1
1
Order By: Relevance
“…The National Prostatectomy Audit 3 found that in nearly half of the cases patients only had creatinine or urea checked either at immediate preoperative assessment or on acute admission for urinary retention. Indeed, 196 (3.7%) of this study group had neither test prior to transurethral resection of the prostate.…”
Section: T He British Association Of Urological Surgeons (Baus)mentioning
confidence: 99%
“…The National Prostatectomy Audit 3 found that in nearly half of the cases patients only had creatinine or urea checked either at immediate preoperative assessment or on acute admission for urinary retention. Indeed, 196 (3.7%) of this study group had neither test prior to transurethral resection of the prostate.…”
Section: T He British Association Of Urological Surgeons (Baus)mentioning
confidence: 99%
“…However, the complications of TURP are also well documented. The National Prostatectomy Audit [1,2] reported a 10% incidence of major inpatient complications, including major bleeding perioperatively (0.7%), and early major haemorrhage requiring return to theatre (0.6%). Over 35% of patients developed complications after discharge from hospital, including clot retention requiring re-admission in 16%.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14,15,16] Although the nosocomial urinary system infection agent microorganisms show variance in the literature, the most commonly seen agent microorganism is reported as E.coli. [12][13][14][15][16]18] An increased multiple antibiotic resistance and in particular increased resistance against quinolones of E. coli is reported. [16,17] Similarly, in our study, E. Coli was the most frequently isolated bacteria, 41 agent microorganisms were isolated in the patients who developed USI.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors which would affect the postoperative complication rates for TURP are reported as prostate size, histology, prostatectomy duration, preoperative bacteriuria, catheterization, surgeries applied simultaneously, previous prostate surgery. [13,14,16,17] When we look at our study, preoperative catheter use among those factors are the significant risk factors in terms of postoperative nosocomial infection development. In the literature, existence of urinary catheter was found as the most important risk factor for the nosocomial infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation